Women entrepreneurs in the circular economy : global experiences - Clausen, Lisbeth (Emerald Publishing Limited, 2025)
Entrepreneurship has long been a way for women to create economic opportunities, especially in challenging environments. Women entrepreneurs are essential in transforming their communities and industries within the global circular economy. By challenging traditional models and addressing urgent issues like environmental sustainability, they are leading a transformative movement that seeks to foster a brighter and more sustainable future for all. In Women Entrepreneurs in the Circular Economy: Global Experiences, author Lisbeth Clausen presents ten compelling stories of women founders across seven different countries, from Japan to Colombia. Their experiences reveal the diverse ways these women navigate barriers in cultural attitudes, access to resources, and work-life balance. Clausen's study is unique for its in-depth ethnographic approach, which includes a novel approach to collaborative immersive fieldwork, interviews, and local expertise. These detailed case studies provide a nuanced understanding of how business acumen, culture, and innovation intersect in the entrepreneurial journeys of these women. By richly exploring diverse cultural contexts and personal narratives, Clausen and her colleagues provide a powerful tool for understanding both the challenges and opportunities women face in the circular economy. This work is essential for anyone interested in culture and diversity studies, entrepreneurship, and sustainable business practices. It serves as a valuable resource for policymakers, educators, and students in higher education, as well as aspiring entrepreneurs seeking global insights.